Identification of a novel missense mutation in NIPAL4 gene: First 3D model construction predicted its pathogenicity. Issue 3 (26th December 2019) - Laadhar, Sahar; Ben Mansour, Riadh; Marrakchi, Slaheddine; Miled, Nabil; Ennouri, Mariem; Fischer, Judith; Kaddechi, Mohamed Ali; Turki, Hamida; Fakhfakh, Faiza
Abstract: Background: The NIPAL4 gene is described to be implicated of Congenital Ichthyosiform Erythroderma (CIE). It encodes a magnesium transporter membrane‐associated protein, hypothetically involved in epidermal lipid processing and in lamellar body formation. The aim of this work is to investigate the causative mutation in a consanguineous Tunisian family with a clinical feature of CIE with a yellowish severe palmoplantar keratoderma. Methods: Four patients were dignosed with CIE. The blood samples were collected from patients and all members of their nuclear family for mutation analysis. The novel mutation of NIPAL4 gene was analysed with several software tools to predict its pathogenicity. Then, the secondary structure and the 3D model of ichthyn was generated in silico. Results: The sequencing analysis of the NIPAL4 gene in patients revealed a novel homozygous missense mutation c.534A>C (p.E178D) in the exon 4. Bioinformatic tools predicted its pathogenicity. The secondary structure prediction and the 3D model construction expected the presence of 9 transmembrane helices and revealed that mutation p.E178D was located in the middle of the second transmembrane helices. Besides, the 3D model construction revealed that the p.E178D mutation is inducing a shrinking in the transport channel containing the mutated NIPA4 protein. Conclusion: We found a homozygous mutation in exon 4 of NIPAL4 c.534A>C (p.E178D), which was identified for the first time in our study. Bioinformatic investigations supported its involvement in the phenotype of patients with CIE. Interestingly, this mutation was located in the hypothetical transport channel cavity and leads to changes in the channel architecture, which would probably affect its transport function. Abstract : Identification of a novel homozygous mutation in NIPAL4 gene in a consanguineous Tunisian family, c.534A>C (p.E178D) causative of Congenital Ichthyosiform Erythroderma (CIE). Bioinformatic investigations supported its involvement in the phenotype of patients. Modeling study revealed that this mutation was located in the hypothetical transport channel cavity and leads to changes in the channel architecture, which would probably affect its transport function.